Numerical Analysis of a Dual-Layer Geosynthetic-Encased Stone Column Installed in Soft Soil - Neeraj Kumar; Rakesh Kumar; Bhawani S. Nirola; Akash Jaiswal (Advances in Civil Engineering)
Stone columns are being used to reduce soft soil settlement and increase load-carrying capacity. Since there is inadequate lateral support from the local native soil, soft soil undergoes excessive settlement under vertical loading. This issue is effectively resolved by suitably encasing stone column material by geosynthetic with significant axial stiffness, which provides the required additional confinement reported in the literature. In the current study, an effort has been made to examine the load settlement behaviour of the dual-layered geosynthetic-encased stone column (DL-GESC) under vertical loading. In order to simulate the behaviour of stone column-reinforced soft soil, a FEM analysis was performed using PLAXIS-3D and three-dimensional (3D) models made utilising the unit cell idealisation technique for a single column. The stone column diameter, spacing to diameter (s/d) ratio, and encasement layers were varied to determine their influence on load-settling behaviour. The vertical load-carrying capacity of the ground was significantly improved when an additional layer of geosynthetic encasement was inserted into the stone column as compared to SL-GESC. Improvement of 15–25% was observed for the analysis of a single column installed in soft clay, according to the result obtained. Improvement ratios have been discussed in detail for various encasement conditions.